2012
DOI: 10.1002/pi.4202
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion and solubility of commercial poly(methyl methacrylate) denture base material modified with dimethyl itaconate and di‐n‐butyl itaconate during water absorption/desorption cycles

Abstract: This study evaluated the water absorption, solubility, kinetics of water diffusion and residual monomer content of commercial poly(methyl methacrylate) (PMMA) denture base material modified with dimethyl itaconate (DMI) and di‐n‐butyl itaconate (DBI). Water absorption and solubility were measured gravimetrically while the residual monomer content was analysed using high‐performance liquid chromatography with ultraviolet detection. It was found that the addition of di‐n‐alkyl itaconates significantly decreases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…In our previous study we have investigated water sorption and residual monomer content in the PMMA denture base materials modified with DMI and DBI [40]. We have found that addition of itaconates reduced water sorption and greatly decreased residual MMA content.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study we have investigated water sorption and residual monomer content in the PMMA denture base materials modified with DMI and DBI [40]. We have found that addition of itaconates reduced water sorption and greatly decreased residual MMA content.…”
Section: Introductionmentioning
confidence: 99%
“…The residual monomer from prepared composites was extracted with methanol in accordance to a procedure previously reported . A Surveyor LC system (Thermo Fisher Scientific, Waltham, MA) was used for the separation of the analyses on a reverse‐phase Zorbax EclipseXDB‐C18 column, 4.6 × 75‐mm internal diameter and 3.5‐μm particle size (Agilent Technologies, Santa Clara, CA).…”
Section: Methodsmentioning
confidence: 99%
“…This was explained by the fact that the methacrylates are more reactive than the itaconates due to the steric hindrance of the alkyl group . Thus, as the copolymerization progress MMA is faster depleted, leading to the significantly lower concentration of the MMA at the end of the reaction . However, the total residual monomer (TRM) concentration was higher compared with the composition containing only MMA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Separation of itaconic acid was performed under isocratic conditions at a flow rate of 1.0 mL min −1 , and we used 2.5% acetonitrile with 0.05% phosphoric acid as the mobile phase. Dimethyl itaconate separation was performed using a gradient of 0–100% methanol with sterilized distilled water at a flow rate of 1.0 mL min −1 . The glucose concentration was determined using a previously described method…”
Section: Methodsmentioning
confidence: 99%